Strategi Inovatif dalam Pembelajaran Agama Islam: Model Kooperatif GQGA untuk Meningkatkan Prestasi Belajar Siswa - Rijal, Samsul (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, dan Publikasi, 2024)
This study aims to determine the improvement of student learning achievement through the Cooperative model of the Giving Question and Getting Answer type. The type of research using Classroom Action Research is carried out in 2 cycles. Each cycle consists of Planning, Implementation, Evaluation and Reflection. The research instruments used are Observation sheets and tests. The subjects of this study were 5th grade students at SDN 1 Montong Betok. Based on the results of the evaluation of student learning completion in cycle I, individually 26 students completed out of 31 students, while classically the value obtained was 83.67%. This means that student learning completion classically has not been achieved. This is in accordance with the success indicators that have been set, namely if 85% of all students get a score of 70 and above. therefore the study was continued to cycle II. In the second cycle, there was a change in the improvement of student learning achievement. While the results of the student learning evaluation, individually 28 students out of 31 students completed. And classically students got a score of 90.32%. So it can be concluded that research with a cooperative model of the giving question and getting answer type can improve student learning achievement in the subject of Islamic Religion for grade 5 of elementary school, especially in the discussion of the law of reading nun sukun and tanwin.